The Economic Consequences of Demographic Change: Its Impact on Growth, Investment and the Capital Stock - Gunther Tichy (Intervention. European Journal of Economics and Economic Policies, 2008)
The traditional debate on the real and financial consequences of ageing is based on two assumptions: a deteriorating old-age dependency ratio and declining productivity of an ageing population. Both suppositions are questionable. Relevant for the future burden is not the old-age dependency ratio but the relation of the working to the non-working part of the population, which will deteriorate only slightly as the number of unemployed and of early pensioners will decline as a consequence of the shrinking working-age population. The productivity of an ageing society may increase even if individual productivity shrinks with ageing: this is a consequence of the increasing disability-free life expectancy and of factor-price induced higher capital intensity. The coming problems of ageing are, therefore, less threatening than suspected in the popular and in parts of the professional literature, especially under some supporting labour market policy.
Keywords: J14; J11; H55; E21; 330; demographic change; ageing society; productivity and saving of the elderly